2015 IEEE Symposium on Computers and Communication (ISCC) 2015
DOI: 10.1109/iscc.2015.7405624
|View full text |Cite
|
Sign up to set email alerts
|

Spectral partitioning for node criticality

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract-Finding critical nodes in a network is a significant task, highly relevant to network vulnerability and security. We consider the node criticality problem as an algebraic connectivity minimization problem where the objective is to choose nodes which minimize the algebraic connectivity of the resulting network. Previous suboptimal solutions of the problem suffer from the computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Among the nodes which lie in the sign cut-set how do we choose the one which is the most critical? In our recent work in [37] we have chosen the node which maximizes the sum of squared…”
Section: Algebraic Connectivity Minimizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the nodes which lie in the sign cut-set how do we choose the one which is the most critical? In our recent work in [37] we have chosen the node which maximizes the sum of squared…”
Section: Algebraic Connectivity Minimizationmentioning
confidence: 99%
“…The criticality of a fixed number of nodes is assessed by evaluating the degradation in performance achieved when these nodes are removed from the network. We conduct a comparative study to investigate the performance of the proposed metric against other approaches that exist in literature such as the betweenness centrality [20], the closeness centrality, the degree centrality [16], the exhaustive search approach, the Hybrid Interactive Linear Programming Rounding (HILPR) metric proposed in [13], the Controllability of complex networks (Cont) approach in [18], the suboptimal solution of Eq (6) which we refer to as the Sum Squared Difference approach (SSD) [28] [29], the suboptimal solution of Eq (7) which we refer to as the Normalized Sum Squared Difference approach (NSSD) [30][31] and our previously proposed approach which we refer to as Spectral Partitioning for Node Criticality approach (SPNC) [37]. Our simulation results indicate that the suboptimal solutions are not conservative and that the proposed criticality metric chooses the most critical nodes in the network as it achieves the greatest degradation in performance when these nodes are removed.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed approach deems a node as critical if it lies in a cutset and experiences the highest traffic flow. A cutset is defined as a set of nodes, that observe a change in sign for the Fiedler vector among their neighbours [2]. The proposed approach is evaluated for change in blockchain size and packet drop ratios and it is observed that the proposed approach outperforms existing approaches by showing a greater reduction in blockchain size and a larger packet drop rate upon removal of the most critical nodes from the network.…”
mentioning
confidence: 99%